Schizophyllum commune - A promising source of lignocellulose degrading enzymes suitable for biodegradation - Thiribhuvanamala, G.; Parthasarathy, S; Ahiladevi, P (Mushroom Research, 2020)
The white rot fungi, Schizophyllum commune a potential degrader of wood but the role of major lignolytic enzymes viz. Laccase (Lac), Lignin peroxidase (LiP) and Manganese peroxidase (MnP) were not studied in detail. Hence, a work was carried out to find out the lignocellullolytic enzyme secretion of S. commune by quantitative and qualitative methods. Sporophores of S.commune collected from wood logs of silver oak trees from Kotagiri was isolated as pure culture and morphologically the fungi could be described as tiny, fan-shaped whitish to grayish pileus, leathery with no stipe and under surface showing split gills and also molecularly characterized (Accession No. JX 885999.1). Solid screening tests with guaiacol showed production of laccase as evidenced by the oxidative polymerization of guaiacol to form reddish brown zones and formation of a green color in the ABTS (2, 2â€™-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) supplemented growth medium was due to the oxidation of ABTS to ABTS-azine in the presence of laccase. The Azure-B agar tests for presence of LiP and MnP showed the faint discolouration of azure-B dye which shows less secretion of peroxidase type of enzymes but however confirms laccase as the major enzyme secreted by S. commune. This study confirmed that S. commune secretes more of Lac followed by LiP and MnP type of enzymes extracellularly. Under liquid screening tests with Lignolysis basal medium S. commune secreted significant levels of laccase at pH of 4.5 LiP and MnP activity at pH of 5.0. A temperature of 30ÂºC was ideal for significant secretion of all the three lignolytic enzymes. However, maximum laccase enzyme secretion occurred at 10th to 12th DAI while LiP and MnP on 6th to 8th DAI, respectively. This study paves way for utilization of S. commune and identification of potential strains for tapping the laccase type of lignolytic enzyme for use in industrial applications.